Perilaku Hidup Bersih Dan Sehat Santri Di Masa Pandemi Covid-19 - Shahibah Yuliani; Nova Scorviana (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Protection of children is very important, especially during the COVID-19 pandemic Theapplication of clean and healthy living behavior (PHBS) is able to reduce the morbidityand mortality of school-age children. DKI Jakarta is a province that has a high number ofCOVID-19 cases and the Duren Sawit sub-district has not been spared the spread of thecase. There are two Qur'an houses where the students stay. Researcher saw that theawareness of students in complying with health protocols is still lacking, Because that theyare often found not wearing masks and like to play outside the dormitory. Therefore, thisresearch article aims to see a description of the clean and healthy living behavior ofstudents during the COVID-19 pandemic with the research subjects of students at TahfidzAl-Maun House and students at Daar El Al-Hufaz. This study uses a descriptivequantitative method through a survey with a Likert scale supported by interviewtechniques. The variables studied were clean and healthy living behavior (PHBS). Thereare three categories of quantitative data analysis, high, medium, and low. The results ofthis study describe the clean and healthy behavior of students in the aspect of consume nutrition food, sports activities, eradicating mosquito larvae, avoid smoking, and weightboddies attention, which is classified as high. Then to ensure the cleanliness of the toiletsand environmental sanitation, draining and cleaning the bathroom, and disposing ofgarbage have moderate criteria. Meanwhile, in terms of hand cleaning, it is still relativelylow